PENGARUH KEMAMPUAN SUMBER DAYA MANUSIA TERHADAP KEBERHASILAN USAHA KECIL DAN MENENGAH - Aini, Widya Nur; Nasution, Ute Ch; Pujianto, Agung (Jurnal Dinamika Administrasi Bisnis, 2019)
This study was prepared to determine the Effect of Human Resource Ability on the Success of Small and Medium Enterprises. Economic development in Indonesia cannot be separated from small and medium enterprises. Small and Medium Enterprises are the backbone of Indonesia's economy which is considered to support the economy in Indonesia. As a support for small and medium enterprises has an important role in the economy such as: able to empower people who do not have jobs (unemployment) and even open opportunities for housewives to participate in small and medium enterprises as an additional knowledge for them and can increase income to help their economy. Empowerment of the community as a human resource is also the first step to prevent more unemployment in Indonesia, one of the reasons for the many unemployed people in Indonesia is because the number of prospective employees who do not qualify to become employees in a company is the reason given. The method used in this study is qualitative, quantitative research, namely research methods based on the philosophy of positivism, used in examining the sample and research population, sample collection techniques are generally carried out by random sampling, while data collection is done by utilizing research instruments that used. Based on the results of the analysis and discussion of the data, the authors obtained conclusions that can be drawn from the research on the Effect of Human Resource Ability on the Success of Small and Medium Enterprises Data obtained from the Ability of Human Resources in the category strongly agree with the mean results of 3.34 on the variable Business Success Small and Medium in the category strongly agree with the results of the mean of 3.41. On quantitative data positive effect obtained significant results 0,000 which shows there is an influence of Human Resource Ability to the Success of Small and Medium Enterprises. Based on the results of the conclusions in the study note that the ability of human resources has a positive effect on the success of small and medium enterprises.Keywords: Human Resource Ability, Success of Small and Medium Enterprises